EKSISTENSI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DALAM MENCEGAH TERBITNYA SERTIPIKAT GANDA DI KANTOR PERTANAHAN KOTA DENPASAR - Made Emy Andayani Citra; I Made Sudirga (Faculty of Law, Mahasaraswati University, Denpasar, 2020)
Land is a very important thing for human survival, this is important because land is usually used to build buildings on it such as buildings, offices, housing and others. Land is important because it is used as a source of livelihood, which is land used as agriculture, animal husbandry, plantations and others. As the population grows, the need for land for residential needs and development needs is increasing, while the area of ​​land is relatively fixed. Although land has many benefits, land can also trigger disputes between people and others, because every human being wants to control the land owned by someone else due to the natural resources contained therein, or because of the value that can be generated from the land.With the increasing number of disputes that occur due to the land, there needs to be a breakthrough in handling it, so that with the issuance of the Systematic Complete Land Registration (PTSL) program it is very feasible to do to at least minimize the land dispute.